Gender and Ethnic Differences in Young Adults' Emotional Reactions to Parental Punitive and Minimizing Emotion Socialization Practices. (April 2017) - Perry, Nicole B.; Leerkes, Esther M.; Dunbar, Angel S.; Cavanaugh, Alyson M.
This study examined differences in how African American and European American participants ( N = 553) recalled feeling when their parents engaged in punitive and minimizing emotion socialization practices during childhood. We conducted this study to replicate and extend previous empirical work by using a more generalizable sample containing both male and female participants and by asking participants to report separately on their mothers and fathers. Results indicated that African American participants reported feeling less hurt and ashamed than European American participants when their mothers and fathers engaged in punitive and minimizing practices. African American participants also reported feeling more loved than European American participants when mothers engaged in punitive and minimizing practices. In addition, gender differences suggested that women feel more hurt and less loved than men when both mothers and fathers engaged in punitive and minimizing emotion socialization behaviors.